Mid-Term Results of Distal Femoral Extension and Shortening Osteotomy in Treating Flexed Knee Gait in Children with Cerebral Palsy - Andreas Geisbüsch; Matthias C. M. Klotz; Cornelia Putz; Tobias Renkawitz; Axel Horsch (Children, 2022)
Background: Distal femoral extension and shortening osteotomy (DFESO) seems to be an effective method for the treatment of flexed knee gait in children with cerebral palsy. Nevertheless, studies investigating the mid- and long-term outcomes after such procedures are lacking in the literature. Therefore, the purpose of this study was to assess the mid-term outcomes regarding sagittal plane kinematics of the knee after DFESO with or without concomitant patella advancement. Furthermore, an evaluation of the postoperative course and possible recurrence of flexed knee gait was planned. Methods: In a prospective observational study, 19 patients (28 limbs; mean age 11.8 years (6.7–16.0 years)) were examined using 3-D gait analysis and clinical exam before (E0) and at a mean of 38 months (E2: 24–55 months) after surgery. Fifteen patients (22 limbs) had an additional first postoperative gait analysis (E1) after a mean of 14 (10–20) months after surgery. In these patients, the postoperative changes between the short-term and mid-term gait analyses were evaluated. Results: DFESO led to a significant decrease in flexed knee gait with an improvement in sagittal plane kinematics during the stance phase. In addition, a slightly increased anterior pelvic tilt was observed at E1, and we found a tendency towards stiff knee gait with a decrease in mean knee flexion in swing at E2. Conclusions: DFESO led to a significant improvement in flexed knee gait in children with cerebral palsy. The therapeutic effect seems to be lasting on mid-term follow-up with a slight overall tendency to recurrence.